(untitled) (Palíndromo, 2023)
This article discusses the transfiguration of appearance in the self-portraits of the series “Between Faces” in a dialogue with the works of the artist Cindy Sherman, as a research problem. The objective is to analyze, in this transfiguration, how the referent, that is, the face, behaves in the modification of appearances. The methodological approach to the creative process is based on Rey’s (2002) three dimensions, namely the abstract, the practical and the work in process. From the resulting series of self-portraits an analysis is made establishing relationships with Sherman’s works. The results show that the transfiguration of appearance and the deformity hide the "artist’s reference" (his face), producing a beauty of another order through which the "artist’s reference" manifests itself (the artist’s specific way of transfiguring his face in the self-portrait). Conclusively, it is perceived that the first referent is camouflaged with a second identity, which is as much his as the first, and which is only revealed when he commits himself to its transfiguration.